Frames e multilingualidade: equivalentes de tradução no dicionário bilíngue do futebol da Copa de 2014 - Ogliari, Cassiane (Universidade do Vale do Rio dos Sinos, 2013)
This research aims at reflecting about the translation equivalents on the soccer domain regarding to a multilingual project based on the fundamentals of Frame Semantics (Fillmore, 1982; 1985). This proposition underlies on the hypothesis that, when dealing with a specific domain, as soccer, in which the conceptual plan of both language is comparable, the lexical equivalences can be observed in a way to privilege the relation between the lexical unit and its frame, which would also be comparable in both languages. To be able to test this hypothesis, this study is subdivided in three chapters: 1) Translation, Language and Culture, that deals with translation equivalence, the different kinds of equivalence and the strategies to define equivalences; 2) Frame Semantics and Cognitive Linguistics, that talks about the principles of Frame Semantics and exemplifies their use when developing a lexical database; and 3) Frames and Multilingualism, that approaches the way in which the concept of frame can influence in multilingual studies and presents the dictionaries Kicktionary and Kickionary_Br 2014 World Cup (project which this dissertation in linked to). The applied part of this research mentions two moments: 1) The analysis of a sample composed by 100 lexical units in English and Portuguese with the objective of verifying the dominant kinds of equivalence with more frequency in our corpus; and 2) The specific reflection about each of the three kinds of equivalence found in corpus. In its last part, this study presents cases of exact equivalence of content, intersection of content and superiority equivalents and ponders about the lexical entries of such equivalences in the soccer dictionary, Kickionary_Br 2014 World Cup.
Keywords: Semântica de frames; Multilingualidade; Equivalência de tradução; Futebol; Dicionário da Copa; Frame semantics; Multilingualism; Translation; Soccer; World Cup dictionary; ACCNPQ::Lingüística, Letras e Artes::Lingüística